2002
DOI: 10.1037/0096-3445.131.4.590
|View full text |Cite
|
Sign up to set email alerts
|

Comment on "Competition for consciousness among visual events: The psychophysics of reentrant visual processes" (Di Lollo, Enns & Rensink, 2000).

Abstract: V. Di Lolo, J. T. Enns, and R. A. Rensink (2000) reported properties of masking that they claimed were inconsistent with all current models. The current authors show, through computer simulation, that many current models can account for V. Di Lollo et al.'s (2000) data. Although V. Di Lollo et al. (2000) argued that their data could be accounted for only with models that incorporate reentrant processing, the current authors show that reentrant processing is not necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 26 publications
1
61
1
Order By: Relevance
“…Common onset masking can be modeled by many of the existing feed-forward and lateral inhibition models of masking (Bischof & Di Lollo, 1995;Francis, 1997;Francis & Hermens, 2002) and by Growney (1978) and Growney et al (1977) experiments. ISI ϭ interstimulus interval.…”
Section: Temporal Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Common onset masking can be modeled by many of the existing feed-forward and lateral inhibition models of masking (Bischof & Di Lollo, 1995;Francis, 1997;Francis & Hermens, 2002) and by Growney (1978) and Growney et al (1977) experiments. ISI ϭ interstimulus interval.…”
Section: Temporal Aspectsmentioning
confidence: 99%
“…Although it has been shown that these aspects can be explained with fairly simple models (Bridgeman, 1978;Francis & Hermens, 2002), often more complex mechanisms were assumed to be necessary, such as dual-channel interactions (Bachmann, 1994;Breitmeyer & Ganz, 1976;Ö gmen, 1993) or recurrent processing . Our results show once more that many temporal aspects of masking can be explained with a simple model structure.…”
Section: Temporal Aspectsmentioning
confidence: 99%
“…They also claimed that notions of reentrant processing are not necessary because all of V. Di Lollo et al 's data can be explained by feed-forward models. The authors show that G. Francis and F. Hermens's claims are vitiated by inappropriate modeling of attention and by ignoring important aspects of V. Di Lollo et al 's results.We note with interest Francis and Hermens's (2002) article, which purports to show that the findings reported by Di Lollo, Enns, and Rensink (2000) can be explained by other models of metacontrast masking. To buttress their claim, Francis and Hermens reported computer simulations showing that some of our results can be modeled by the theories of Bridgeman (1978), Francis (2000) and Weisstein (1968).…”
mentioning
confidence: 99%
“…The answer is yes if one is willing to hypothesize that increases in set size lead to distributed attention, which makes the mask signal have a larger impact on the target signal (see Francis & Hermens, 2002). Figure 6B shows simulation results that demonstrate this property.…”
Section: Models Availablementioning
confidence: 99%
“…The key effect was that strong masking could occur for a spatially impoverished mask (four dots around a target) when the target and the mask had common onsets but the mask stayed on after the target disappeared. The new effect is quite interesting and is a new experimental finding; however, Francis and Hermens (2002) showed, through computer simulation, that some of the quantitative models of masking can account for the effect without a change in parameters. Thus, even mathematically sophisticated researchers have proposed their own quantitative model) may not recognize the properties of existing quantitative models of backward masking.…”
mentioning
confidence: 99%